Pasteuriza̧ão de turfa brasileira para o cultivo de Agaricus brasiliensis - Colauto, Nelson Barros; Da Silveira, Adriano Reis; Da Eira, Augusto Ferreira [UNESP]; Linde, Giani Andrea (Universidade Estadual de Londrina, 2010)
Agaricus brasiliensis is a Brazilian basidiomycete which has been cultivated and consumed around the world as a therapeutic food. Casing layer is one of the most important steps on A. brasiliensis cultivation and European peat is the most used casing layer on Agaricus bisporus cultivation. Besides the importance of it on mushroom cultivation the peat import could be a risk of exotic organism introduction. Alternative as Brazilian peat is barely used for mushroom growers in Brazil. Thus, the objective of this work was to evaluate Brazilian peat with and without pasteurization as casing layer on A. brasiliensis cultivation. The fungus was previously grown on wheat grains and transferred to a substratum prepared by composted traditional method. After mycelium colonization of the substratum a pasteurized or non pasteurized Brazilian peat (casing layer) was added. It was concluded that pasteurization of the casing layer increases in 30% yield after 65 days of cultivation. There is no difference of yield for pasteurized and non pasteurized casing layer until 30 days of cultivation. An increase of flies is observed in non pasteurized casing layer. The production flush is easily perceived with pasteurized casing layer but not with non pasteurized casing layer.
Pasteurization of Brazilian peat for Agaricus brasiliensis cultivation
Keywords: Biological efficiency; Flies; Mushroom; Production flush